Navigating sexual norms abroad: Cultural values, sex education, and risk among international students in China - Liang, Jinyu; Yahaya, Mahathir (Journal of International Students, 2026)
International students often navigate unfamiliar sexual norms and limited access to context-specific sex education while studying abroad. This study examines how traditional sexual values and inadequate sex education shape sexual behaviors and vulnerability to sexual victimization among international students in China. Using a mixed-methods design, data from 482 students and 20 interviews were analyzed. Findings reveal a paradox: traditional values were linked to lower sexual activity but also reduced awareness of safe sex practices. Inadequate sex education was associated with greater sexual risk behaviors. Both factors increased vulnerability to sexual victimization, with sexual behavior mediating these relationships. The findings underscore the need for culturally responsive sex education, consent awareness, and targeted support services for international students.